A Forecasting Methodology as Applied to Financial Time Series. - Mabert, V.A.; Radcliffe, R.C. (The Accounting Review, 1974)
Presents information on a study which described the application of Box-Jenkins methodology to the problem of forecasting financial time series data. Description of the generalized model; Methodology; Results and discussion; Conclusions.